Performance dynamics of international exchange-traded funds - Stephen Bahadar; Christopher Gan; Cuong Nguyen (Journal of Risk and Financial Management, 2020)
Asynchronous trading hours between the markets of Exchange-Traded Funds (ETFs) and their benchmarks not only make it difficult to apply a full replication strategy but also make the creation/redemption process ineffective and consequently distress the performance of international ETFs. Despite the exponential growth of the ETF industry in general and international ETFs in particular, the performance of international ETFs is under-researched. Therefore, this study evaluates the performance of US-listed international ETFs by analyzing the returns, volatilities, tracking ability and pricing efficiency. The study findings are useful for investors interested in understanding the performance dynamics of international ETFs.
Keywords: 330; ETFs; premium and discount; return and volatility; tracking error